Cuttlefish bone optimization in foam concrete / Daliah Hasan, Mohd Zaini Endut and Fazrul Azree - Hasan, Daliah; Endut, Mohd Zaini; Azree, Fazrul (2020)
Improving and studying other foam concrete along with marine-based cuttlefish bone can be an creative way and a good choice to be included in a concrete as sufficient cementitious materials to provide environmental friendliness. In this regard, lightweight foam concrete was produced to determine its compressive strength using different percentages of cuttlefish bone as an additive. The overall strength performance of foam concrete with cuttlefish bone addition is calculated and analysed in this research. The percentage of cuttlefish bone as an additive was determined by total cement weight, such as 0%, 1%, 2%, 3%, and 4% were applied to various 900 kg/m3 and 1800 kg/m3 foamed concrete densities. As a result, it gives a compressive strength value greater than standard foam concrete without an additive by referring to the results obtained when 2% of cuttlefish bone was applied to the foam concrete of 1800 kg/m3 specimens. The compressive strength tends to gain late strength for 900 kg/m3 foam concrete specimens. It can be concluded that the optimum quantity of cuttlefish bone additive required to increase the early strength is 2% and excessive percentage of additive amount would be degraded the strength of foam concrete.